Therapeutic Potential of Secretome from Hypoxic-Mesenchymal Stem Cell (SH-MSC) in Regulating PDGF and IL-1β Gene Expression in Fluconazole-Related Alopecia - Jessika, Cleveria; Putra, Agung; Sumarawati, Titiek (Biosaintifika: Journal of Biology & Biology Education, 2024)
Fluconazole long therapy causes severe alopecia by increasing interleukin-1ß (IL-1ß) and decreasing platelet-derived growth factor (PDGF). Secretomes from hypoxic mesenchymal stem cells (SH-MSCs) contain anti-inflammatory and growth factors that potentially aid in repairing damaged hair follicles. Therefore, this study aimed to analyze the effect of SH-MSCs on PDGF and IL-1β gene expression to develop a more effective alopecia therapy with minimal side effects. MSCs were extracted from the rat's umbilical cord and cultured under hypoxic conditions for 24 hours before secretome collection. The experiment used six rats per group for a positive control placebo (K1), a negative control group treated with fluconazole + placebo (K2), and topical gel containing 10% and 20% SH-MSCs for K3 and K4, respectively. The rat's PDGF and IL-1β gene expression was measured after 29 days of treatment and validated using histopathological analysis to evaluate hair follicles. The results showed that SH-MSC application significantly increased PDGF and decreased IL-1β gene expression (LSD test result p < 0.001). The highest expression of PDGF was observed in K4, which is 1.71 ± 0.31 fold change, followed by K3 with 0.806 ± 0.12 fold change. Conversely, IL-1β mRNA expression was significantly decreased in K4, which is a 1.41 ± 0.20 fold change, followed by K3 with a 2.71 ± 0.23 fold change (Mann-Whitney test result p < 0.001). Applying SH-MSC improved hair follicle tissue by increasing anagen cell type than telogen. This study indicates that SH-MSCs have the potential to be developed as a topical gel for the treatment of fluconazole-related alopecia.